Arabs, politics, and performance
1 online resource (xiii, 291 pages).
Keywords: "This collection is a ground-breaking collection on contemporary Arab theatre. Through four sections discussing Occupation and Resistance, Migration and Refugees, Religion and Secularism, and Nationalism and Belonging, this study provides nuanced responses to the contested points of intersection between Arab culture and the West, as well as many of the major concerns within contemporary Arab theatre. The collection draws together scholars from the Middle East, North Africa, Europe, and the United States who write about Arab theatre and the representation of Arabs on European and American stages. It introduces concerns in contemporary Arab theatre, the regions in which Arab theatre is performed, and the issues with representations of Arabs onstage. This volume will be of great significance for those interested in expanding the range of global, postcolonial, African, Asian, or diasporic theatre that they study, teach, or stage"--